Influence of nanosilica particles on the high-temperature performance of waste denim fibre-modified bitumen - Al-Sabaeei, A.M. (Taylor and Francis Ltd., 2022)
In this study, separate and composite nanosilica (NS) and waste denim fibre (WDF) are utilised to improve the rutting performance of bitumen. The effects on the rheological properties of base and modified bitumen before and after short-term aging were investigated. Conventional tests were performed to check the feasibility of the composite modified bitumen to be utilised as a flexible pavement material. Rolling thin film oven, temperature sweep test and multiple stress creep recovery (MSCR) tests were conducted to assess the effects of NS, WDF and composite NS-WDF on advanced rheological properties. Results show that the addition of NS to WDF-modified bitumen improves the conventional characteristics and rutting resistance parameters. MSCR test results indicate that increased in both NS and WDF content leads to a decline and increase in the non-recoverable creep compliance and percentage recovery respectively. The performance grade of bitumen was improved from PG 64S to PG**V for composite NS-WDF-modified binders at both 4 NS and WDF. The WDF provides more elastic contribution compared to the NS. This can be ascribed to the presence of clumps/clusters of fibres in the blends acting as pockets of elasticity. These findings reveal the remarkable improvement in rutting resistance and elasticity of bitumen. Â© 2020 Informa UK Limited, trading as Taylor & Francis Group.